The Politics - Aristotle (Cambridge University Press, 1988)
This new edition of The Politics provides students with an unusually lucid and accessible account of this complex, difficult and enormously influential work. It is based on Jonathan Barnes' revision of the renowned Jowett translation, and includes detailed note, a guide to further reading and a chronology of the principal events in Aristotle's life. In his introduction Stephen Everson tackles those problems most likely to hamper students in understanding The Politics. Aristotle's political theory is closely related to claims and types of explanations which he uses and justifies elsewhere in his works, and so one of Everson's main purposes is to show how Aristotle's arguments can best be grasped through an understanding of what he has to say in The Physics about nature and in the The Ethics about human flourishing.